The Federal Reserve System : purposes and functions - Board of Governors of the federal reserve system (Washington, D.C. : Board of Governors of the Federal reserve system, 1961)
This book is dedicated to a better public understanding of the system's trusteeship for the nation's credit and monetary machinery. It described the system's organization, the range of its operations, and it contribution to stable economic progress.
Includes index.
hza 28/01/2019
Loans
Keywords: Banks and banking; Federal Reserve banks; United States